2012
DOI: 10.4236/wjns.2012.22016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in reaction time, coefficient of variance of reaction time, and autonomic nerve function in the mental fatigue state caused by long-term computerized Kraepelin test workload in healthy volunteers

Abstract: Fatigue is a common sense caused by crushing labor, stressful social events and various illnesses. It is usually judged by their subjective symptoms, but it should be evaluated in an objective perspective. Here we show that the decrease of working efficiency and sympathetic hyperactivity are associated with mental fatigue state caused by prolonged mental workload. Recently we made a new mental fatigue model of healthy volunteers caused by long-term computerized Kraepelin test (CKT) workload. CKT is our new sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…However, the sympathetic nervous system was in a dominant state in these individuals, with a high LF/HF ratio, which is an indicator of the autonomic nervous system balance, exceeding the normal value of 2.0. Previous studies have shown that Uchida-Kraepelin stress affects heart rate variability [31][32][33][34]. We selected subjects who felt that taking the Uchida-Kraepelin test was stressful had a substantial increase in their LF/HF ratios.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sympathetic nervous system was in a dominant state in these individuals, with a high LF/HF ratio, which is an indicator of the autonomic nervous system balance, exceeding the normal value of 2.0. Previous studies have shown that Uchida-Kraepelin stress affects heart rate variability [31][32][33][34]. We selected subjects who felt that taking the Uchida-Kraepelin test was stressful had a substantial increase in their LF/HF ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is defined as a decline in the ability and efficiency of mental and/or physical activities [ 2 , 3 ]. In other words, maintenance of work efficiency indicates that fatigue is being suppressed [ 4 , 41 , 42 , 43 ]. There was no significant difference in the rate of correct responses in the 2-back tasks between the two groups, suggesting that the fatigue loading due to work was evenly distributed between the two groups and that EOD-1PM intake reduced fatigue due to workload.…”
Section: Discussionmentioning
confidence: 99%
“…The results of recent studies revealing sympathetic hypertonia and reduced autonomic nervous activity among teachers in a state of chronic fatigue and workers experiencing stress imply that evaluation of autonomic nervous function may be an effective means of measuring objective fatigue. However, age greatly influences autonomic nervous activity among individuals, making it difficult to apply this method to groups with members of different ages [9, 10, 30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic hyperactivity based on decreased parasympathetic activity has also been found to be associated with mental fatigue induced by prolonged cognitive load [8]. Furthermore, when we assessed autonomic function in a mental fatigue model of healthy volunteers caused by long-term computerized Kraepelin test workload, the low/high frequency component ratio (LF/HF) was significantly increased by the fatigue-inducing task and decreased by resting, suggesting that mental stress causes a relatively sympathetic nerve activity-dominant state [9]. When we studied autonomic nerve function in patients with chronic fatigue syndrome, we found that as the symptoms of fatigue became stronger, parasympathetic nervous activity decreased.…”
Section: Introductionmentioning
confidence: 93%